G50(P) Getting to the heart of the white matter. (25th October 2020) - Morgan, I; Herbert, C; Forbes, K; O'Regan, M; Hunter, L; Forrest, K
Abstract : Objective: Acute Disseminated Encephalomyelitis (ADEM) is an immune mediated inflammatory CNS disorder, predominantly affecting white matter, with a wide differential. 1 Here we describe a rare mimic of ADEM that is essential to consider in order to avoid catastrophic outcome. Case History: A 12-year old girl presented with a 2 day history of confusion, dysarthria, ataxia and left-sided squint, preceded by 12 days of being generally unwell, with headache and lethargy. Examination confirmed encephalopathy and left third cranial nerve palsy. MRI brain was suggestive of ADEM and MRI spine was normal. A recommended work up for ADEM 1 was performed. Rapid resolution of her symptoms occurred following treatment with intravenous methylprednisolone for three days. 2 years later she presented with acute left lower limb ischaemia and underwent emergency embolectomy of a popliteal arterial obstruction; with myxomatous material identified. Preoperative echocardiogram confirmed left atrial mass which was then surgically removed. Pathology confirmed an atrial myxoma (AM). Retrospective review of her initial MRI images concluded that embolic phenomena from the AM was the most likely explanation of her first presentation. Conclusions: AM is a very rare primary cardiac tumour and left sided AM can embolise to the cerebrovascular system. 12% of adults with AM present with neurological symptoms, and this can mimic multiple sclerosis. AM presenting with acute neurological symptoms masquerading as ADEM in paediatrics has not previously been reported. Early identification of AM is important as, untreated, it can cause multiple embolic events and sudden cardiac death. Careful follow up is essential as late neurological complications (including cerebral arterial aneurysms) are recognised. This case highlights that ADEM is a diagnosis of exclusion, and that mimics for acute focal neurology with encephalopathy and T2 hyperintensities on MRI require careful consideration, including embolic phenomena. Clinical examination alone does not exclude AM and consideration of echocardiography is recommended. Reference: Differential diagnosis and evaluation in paediatric inflammatory demyelinating disorders. Neurology 2016 (Suppl2);87:S28–37.